Toxicity profiles between strains of Alexandrium Tamiyavanichii - Muhamad Bunnori, Noraslinda; Mohammad Noor, Normawaty; Abd Hamid, Shafida; Hamdan, Nurul Ashima; Abu Hassan, Muhamad Shafiq (2018)
Phycotoxins are byproducts of toxic microalga that capable of causing severity on humans upon consuming contaminated seafood. The amount of toxins released by microalgae varies according to species as some of the microalgae synthesize toxins within small number of cells while others required a blooming event for the toxins to be detected. It is also possible for the toxicity of one species being gradually decreases throughout years in culture. Alexandrium tamiyavanichii has been reported to cause toxicity in seafood products that subject to hospitalized cases in Malaysia. Genus Alexandriumhas been known for its stability in producing toxins yet no total loss of toxicity has been recorded. Two cultures of A. tamiyavanichii have been tested for its toxicity using high-performance liquid hromatography (HPLC) with GTX standards as reference. Strains isolated from Kuantan Port during recent cases of paralytic shellfish poisoning (PSP) outbreak showed extremely high in total toxin content (3.07 nmol.cell-1) while the clonal culture of A. tamiyavanichii established from Sebatu Malacca exhibited very low level of toxicity (1.167 fmol.cell-1). There are many factors influencing toxicity properties of A. tamiyavanichii with highlights in nutrients deprivation and adaptation as well as bacterial influences for the aged culture.